Identification of Medicinal Chemicals (BKO) Piroxicam in Jamu Pegal Linu Preparations in Makassar City - Hasnaeni, Hasnaeni; Handayani, Selpida; Andina, Velda (Universitas Pendidikan Mandalika, 2024)
The aim of the research was to identify Piroxicam in herbal medicine for rheumatic pain circulating in Makassar. There are several traditional medicines that contain medicinal chemicals. Research has been conducted on the identification of medicinal chemicals (BKO) on several rheumatic herbs preparations in herbs shops in Makassar. The BKO which is often included in rheumatic herbs is the NSAID group, one of which is piroxicam. This inspection was conducted to know the presence of the chemical drug piroxicam contained within rheumatic herbs preparations and the samples used were 5 samples. The method used was a qualitative test using thin layer chromatography (TLC) consisting of a mobile phase mixed with n-hexane and acetone (7:3) and a stationary phase using Silica Gel GF254. The results of the TLC examination from 5 samples of herbal medicine added BKO piroxicam contained 3 samples including herbs A, B, and C because they had the same stain color at the same Rf value as the piroxicam. Some of the rheumatic herbs circulating in Makassar contain medicinal chemicals in the form of piroxicam.